Smart Heat-health Action Plans: A Programmatic, Progressive and Dynamic Framework to Address Urban Overheating - Ghosh, Aveek (Geographica Pannonica, 2024)
Cities stand at the focal point of vulnerability to heat waves (HWs) as they threaten urban livability and sustainability. National, regional, and local heat-health action plans (HHAPs) are vital for combating HWs and are increasingly crucial as adaptation measures to extreme heat. The present article highlights the most recent development on the working mechanism of HHAPs, its contemporary challenges, barriers to it and a range of operational heat management and planning strategies. It introduces the concept of ‘smartness’ to the existing mechanism of HHAPs which holds a significant potential to be intelligent, explicit and dynamic to address the growing and multifaceted impacts of extreme heat. It emphasizes urgent priorities including long-term heat planning, multisectoral heat-early warning systems, building urban heat resilience and recommends the application of eight core elements endorsed by the World Health Organization (WHO) for effective implementation of HHAPs. Collaboration among meteorological, epidemiological, public health, and urban planning experts is essential for addressing the multidimensional challenges of extreme heat.